Multiple analogies in science and philosophy - Shelley, Cameron (Human cognitive processing ;, 2003)
A multiple analogy is a structured comparison in which several sources are likened to a target. In Multiple analogies in science and philosophy, Shelley provides a thorough account of the cognitive representations and processes that participate in multiple analogy formation. Through analysis of real examples taken from the fields of evolutionary biology, archaeology, and Plato's Republic, Shelley argues that multiple analogies are not simply concatenated single analogies but are instead the general form of analogical inference, of which single analogies are a special case. The result is a trul.